The philosophy of Constantine the Philosopher of Nicaea - Eisenberg, Merle (Byzantinische Zeitschrift, 2021)
The two extant works of Constantine the Philosopher of Nicaea reveal a late twelfth century thinker of the Neoplatonic sensibility typically seen only in those who reached the pinnacle of Byzantine literacy during this period. We argue that he is of particular interest because he coined two philosophical terms that, while mirroring controversial Neoplatonic concepts, better accommodate their Orthodox acceptance.We offer here some background on the author, a short discussion of the philosophical content of these works, and for the first time an English translation of both texts.